2007
DOI: 10.1002/bjs.6049
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility in pancreatic ductal adenocarcinoma

Abstract: There is great scope for further investigation of critical pathways and unidentified genetic influences may be revealed. This may eventually allow the identification of individuals at high risk who might be targeted for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…No association between the risk of AP and family history was detected in this study (Table 1). It is indicated that smoking status, duration and intensity were risk factors for AP by the researchers [2527]. We found that there was a weak association between cigarette smoking and development of AP in the study population (OR = 1.59; 95% CI: 0.89−2.84; P = .075) (Table 1).…”
Section: Discussionmentioning
confidence: 69%
“…No association between the risk of AP and family history was detected in this study (Table 1). It is indicated that smoking status, duration and intensity were risk factors for AP by the researchers [2527]. We found that there was a weak association between cigarette smoking and development of AP in the study population (OR = 1.59; 95% CI: 0.89−2.84; P = .075) (Table 1).…”
Section: Discussionmentioning
confidence: 69%
“…This interindividual genetic variation modulates risk for malignancy [15] and identification of these genetic differences forms the basis of risk stratification thereby enabling targeted prevention or earlier diagnosis [16, 17]. This is especially pertinent to pancreatic cancer, as it has a particularly poor prognosis and palliation of symptoms is the most common therapy patients receive—mainly because of late diagnosis although there are other biological factors that play a role.…”
Section: Introductionmentioning
confidence: 99%
“…For the nonfamilial (sporadic) pancreatic cancer, a few low penetrance genes have been identified by genome-wide association studies (GWAS). Pancreatic cancer candidate genes have also been reported from studies that examined the biological pathways known to be important in the development of pancreatic cancer, for example, tobacco metabolism, DNA repair, inflammation, and folate metabolism [19, 20]. …”
Section: Discussionmentioning
confidence: 99%